2020
DOI: 10.1590/1414-431x20199058
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function after total laparoscopic hysterectomy or transabdominal hysterectomy for benign uterine disorders: a retrospective cohort

Abstract: The objective of this study was to evaluate changes in sexual function after total laparoscopic hysterectomy (TLH) or transabdominal hysterectomy (TAH). This retrospective cohort study included patients with benign uterine tumors that were divided into TLH group and TAH group based on the hysterectomy technique used. Baseline, intraoperative, and postoperative characteristics were compared between groups. Postoperative sexual function was assessed using the Brief Index of Sexual Functioning for Women. The TLH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Wang concluded that total hysterectomy has a negative effect on women's sexual function by reducing the frequency of sexual activity, decreased libido, orgasmic dysfunction, and increased dyspareunia (8). In contrast, other reports suggest that hysterectomy can improve female sexual function because it reduces symptoms associated with benign conditions such as bleeding problems, dyspareunia, prolapse-related reluctance, fear of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Wang concluded that total hysterectomy has a negative effect on women's sexual function by reducing the frequency of sexual activity, decreased libido, orgasmic dysfunction, and increased dyspareunia (8). In contrast, other reports suggest that hysterectomy can improve female sexual function because it reduces symptoms associated with benign conditions such as bleeding problems, dyspareunia, prolapse-related reluctance, fear of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast Wang et al [41] analyzed a retrospective chinese study between abdominal and laparoscopic hysterectomy using the Brief Index of Sexual Functioning for Women (BISF-W) [36]. The authors found lower sexual satisfaction after surgery in both groups with no significant difference between them in any of the indexes of postoperative sexual function.…”
Section: Sexual Function Related To Surgical Approachmentioning
confidence: 97%
“…Small number of studies have reported than postoperative sexual function is comparable between open or laparoscopic approach with similar negative effects in patients undergoing hysterectomy for benign conditions [41][42][43][44][45][46], A chinese retrospective study for benign tumors found no significant differences between open or laparoscopic hysterectomy, reporting for both groups decreased satisfaction with sexual life, reduced frequency of sexual activity, decreased libido, orgasm dysfunction and increased dyspareunia after hysterectomy [41]. Prospective studies in turkish population [43][44][45] also revealed a detrimental effect using validated pre and postoperative questionnaires, without differences for the two different hysterectomy techniques.…”
Section: Sexual Function Related To Surgical Approachmentioning
confidence: 99%
“…Women often see the uterus as a sexual organ that controls and regulates important physiological functions in the body and a source of youth, energy, activity, and a symbol of fertility. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%